2020
DOI: 10.1101/2020.08.27.270843
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A dissemination-prone morphotype enhances extrapulmonary organ entry by the fungusCryptococcus neoformans

Abstract: SUMMARYPhenotypic heterogeneity is a common microbial strategy to improves fitness in fluctuating environments. The fungal pathogen Cryptococcus neoformans exhibits dramatic size heterogeneity: it varies from 2-100 μm in diameter during mammalian infection. Following pulmonary invasion, cells enlarge to >30 μm diameter, then decrease over disease course. Extrapulmonary organs, particularly the brain, contain uniformly small cells, implying that that morphotype is important for dissemination. To test this hy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 149 publications
(250 reference statements)
0
2
0
Order By: Relevance
“…Quantification was performed using a FACS ARIA III (BD) cytometer with analysis on the Cytobank platform. A total of 20,000 events were recorded, and doublets were filtered out using comparisons of forward-scatter width (FSC-W) versus forward-scatter height (FSC-H) to exclude events with high FSC-W and FSC-H. To define the 1C and 2C gates, cells were grown in yeast nitrogen base (YNB) (24 h, 30°C, 150 rpm) without or with 80 μg/ml benomyl, which traps cells in 2C, as recently reported ( 106 ).…”
Section: Methodsmentioning
confidence: 99%
“…Quantification was performed using a FACS ARIA III (BD) cytometer with analysis on the Cytobank platform. A total of 20,000 events were recorded, and doublets were filtered out using comparisons of forward-scatter width (FSC-W) versus forward-scatter height (FSC-H) to exclude events with high FSC-W and FSC-H. To define the 1C and 2C gates, cells were grown in yeast nitrogen base (YNB) (24 h, 30°C, 150 rpm) without or with 80 μg/ml benomyl, which traps cells in 2C, as recently reported ( 106 ).…”
Section: Methodsmentioning
confidence: 99%
“…2 Multiple in vitro conditions induce the growth of cryptococcal capsule. [5][6][7][8][9][10] Conditions that reflect aspects of the mammalian host environment are of particular interest, such as those that include tissue culture medium (TCM) or mammalian serum 9 , human body temperature (37°), host-like CO2 concentrations (~5%) 6 , host-like pH (7.35-7.45), 6,[9][10][11][12] and nutrient limitations typical of the host environment. 7 We have previously shown that transcription is required for capsule growth.…”
mentioning
confidence: 99%